Relevance of routine abdominopelvic ultrasound in suspected child abuse in children under 2 years of age: review of 15 years of experience - Martin-Champetier, Antoine (Child maltreatment, 2022)
In France, the current recommendation is to perform a routine abdominopelvic ultrasound in any child under 2 years of age who is suspected to have been abused. We retrospectively studied the relevance of this practice in our center over the past fifteen years. This was a descriptive, retrospective study of all children under 2 years of age who had been subject to suspected abuse. Abdominal images and reports were reviewed and cross-referenced with possible clinical and biological signs. Four hundred and five children were included between 2006 and 2020, of whom 296 underwent abdominal imaging (2 initial abdominopelvic CT scans, 4 ultrasounds followed by CT scans, and 290 ultrasounds alone). Four examinations revealed traumatic abnormalities related to abuse. These four children all had clinical or biological anomalies. In the absence of clinical or biological signs, no imagery showed any abnormality related to abuse.